Association of pyuria and positive urine culture in children with urinary tract infection - Adrian Umboh; Andy Sugoro (Indonesian Pediatric Society, 2002)
Background Infections affecting the urinary tract are commonly found in children and responsible as the second cause of morbidity after respiratory tract infections.Objective To detennine the association between pyuria and positive urine culture in children with suspected urinary tract infection (UTI).Methods We reviewed all patients who suffered from suspected UTI with pyuria, aged 1 month to 13 years at the Department of Child Health, Manado Central General Hospital from January 1999 until December 2001.Results Of the 45 patients who suffered from suspected UTI with pyuria, 33 (73%) were proved to have UTI (12 males and 21 females). There was significant association between pyuria of more than 20 white cells per high power field visualized and the incidence of UTI (P <0.05), but no association was found between sex and the incidence of UTI. In patients aged 1 year and older, the rate of UTI was higher in female than male, namely 61 % of females and 30% of males had UTI. The main cause of UTI was Escherichia coli (67%). The most common symptoms were fever (94%), vomiting (76%), and upper abdominal pain (55%).Conclusion There was a significant association between patients whom suspected UTI with pyuria and incidence of UTI.